Personal Data Leaks Ahead of 2024 Elections: Threats to Integrity and Public Trust - Muh. Akbar Fhad Syahril; Dina Maliah Hasan; Nurhaedah Hasan (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the effectiveness of personal data protection in Indonesia, especially ahead of the 2024 General Election, with a focus on Undang-Undang Perlindungan Data Pribadi. Although the Undang-Undang PDP has provided a comprehensive legal framework, the results of the study show that challenges in its implementation are still significant, such as data leak incidents and weak law enforcement. The recommendations produced include increasing socialization and education, strengthening supervisory institutions, and collaboration between the government, institutions, and the community. With joint efforts, it is hoped that personal data protection can be improved so that the community feels safe in participating in the democratic process